1987
DOI: 10.1161/01.hyp.10.5_pt_2.i37
|View full text |Cite
|
Sign up to set email alerts
|

Genetic studies of cation tests and hypertension.

Abstract: SUMMARY Several tests of cation concentration and transport are being studied among members of large Utah pedigrees as part of a study of the genetic and environmental determinants of essential hypertension. Corrected urinary sodium excretion and plasma sodium concentration correlated well in spouses and siblings (r = 0.21-0.54, p< 0.001), suggesting the effects of shared family environment (e.g., sodium intake). Intraerythrocytic sodium concentration and sodium-lithium countertransport showed no significant c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

1
0
0

Year Published

1989
1989
2003
2003

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(1 citation statement)
references
References 29 publications
1
0
0
Order By: Relevance
“…We have to emphasize, however, that sodium-proton exchange and SLC do not necessarily reflect the same phenotype or genotype 21 and that SLC is, between these, the most studied transport system in epidemiological investigations on predictors of hypertension. 30,36,37 On the other hand, in agreement with our results, Falkner et al 38 have demonstrated a relationship between UAE rate and SLC in young adult African Americans with borderline to mild hypertension.…”
supporting
confidence: 93%
“…We have to emphasize, however, that sodium-proton exchange and SLC do not necessarily reflect the same phenotype or genotype 21 and that SLC is, between these, the most studied transport system in epidemiological investigations on predictors of hypertension. 30,36,37 On the other hand, in agreement with our results, Falkner et al 38 have demonstrated a relationship between UAE rate and SLC in young adult African Americans with borderline to mild hypertension.…”
supporting
confidence: 93%